Investing in Social Capital: The Ifugao Cultural Practices Builds Bonding, Bridging, and Linking amidst Pandemic - Moraya Caclini Pumihic (Universidade Estadual de Alagoas, 2023)
Social capital is akin to actual capital in that people with more money are typically better off and have easier access to investment opportunities.  The purpose of the study is to determine how and why communities in Ifugao continue to invest in social capital in their cultural practices.  Ethnography as a qualitative design, is the inquiry used in this study. Participant's observation, along with interviews and coupled with focus group discussion are the tools used in collecting data.  The data gathered were analyzed using thematic analysis.  Findings revealed that majority of the performers and participants are above 55 years old, male, married, college graduates, government employees, and have a monthly salary of over 40,000 Php.  Most of the attendees to Ifugao birthdays, engagements, weddings, and death wakes perceived that non-monetary benefits were achieved such as strengthening bonds between families and close friends, bridging links with faraway friends, and connecting relationships with other participants.  In terms of investment, the wedding has a high cost, high return, and high return monetary value, while death has a low cost and high return monetary value.  Ifugao (Tuwali) cultural community invest in social capital strengthen their families, friends, and communities' bonds, connections, trust, and reciprocity.